Cortical activation associated with asterixis in manifest hepatic encephalopathy. (24th December 2013) - Butz, M.; Timmermann, L.; Gross, J.; Pollok, B.; Südmeyer, M.; Kircheis, G.; Häussinger, D.; Schnitzler, A.
<x xml:space="preserve">Abstract</x> Objectives Severe hepatic encephalopathy gives rise to asterixis, a striking motor symptom also called flapping tremor, which is characterized by a sudden ceasing of muscle tone in all muscles of a limb. In this study, we aimed at scrutinizing the cortical activation associated with asterixis and unraveling the underlying pathophysiological mechanisms. Material and methods We recorded simultaneously neural activity with magnetoencephalography (MEG) and muscle activity with surface EMG in nine patients with manifest hepatic encephalopathy showing asterixis. Asterixis events were detected semiautomatically and served as triggers for averaging MEG signals. Evoked responses averaged time‐locked to asterixis events were subjected to equivalent current dipole (ECD) modeling. Additionally, we localized the strongest cortico‐muscular coherence in the frequency of the co‐occurring tremulousness. Results Evoked fields averaged time‐locked to asterixis events were best explained by a single dipolar source in the contralateral primary motor cortex (M1, Talairach coordinates of mean localization: −40, −20, and 64; Brodmann area 4). This dipole showed a twofold field reversal, that is biphasic wave, with frontal dipole orientation at 49 ms before flap onset and 99 ms after flap onset. Conversely, two maxima with occipital dipole orientation were observed 2 ms and 160 ms after flap onset. Cortico‐muscular coherence for the tremulousness was likewise localized in the contralateral M1 confirming earlier findings in the present patient cohort. Conclusions Our results reveal an involvement of M1 in the generation of asterixis. As also tremulousness, also called mini‐asterixis, was shown to originate in M1, asterixis and mini‐asterixis may share common pathophysiological mechanisms.